Tenho raiva da escola: o olhar dos adolescentes sobre as relações escolares - Melo, Anniely Laís Lima (2018)
The present study is inserted in the debate about the events that arouse the anger in adolescents at school. In this sense, the research aims to analyze the stimuli that arouse anger in the view of the adolescents, and its impacts in the school. The research was carried out with students of the Municipal School David Trindade in the city of João Pessoa PB. In this study, anger (or ire) is understood as a protective emotion, and an act of self-defense of dignity, rights and integrity, which is triggered by a threat and can be expressed as irritation, fury or wrath. Associated with the emotion of hostility, anger produces aggressive attitudes. In this study, was registered the existence of processes of disqualification of the other as an expression of anger, highlighting disqualification practices such as gossip, nickname and name-calling, identified as verbal violence and instituting forms of power relations. This is a qualitative research with the Grounded Theory approach, conducted through semi-open questionnaires and a semi-structured interview with adolescents of the David Trindade Municipal School in Paraíba. In this dialogue, we present the contributions of authors like Rafael Bisquerra (2000), Enrique Abascal (2015), Giovanni Frazzetto (2014), Norbert Elias (2000), Mira y López (2012), Mariani (2014), García and Arellano (2006). The results of the research show the protective character of group relationships and the identification of the emotion of empathy as an inhibitory element of aggressive practices in school.